PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION PADA SISWA KELAS VII.6 DI SMP NEGERI 1 RAMBAH - Almi Yelli (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to see whether the Realistic Mathematics Education (RME) approach can improve the activity and learning outcomes of grade VII.6 students in PLSV material in SMPN 1 Rambah in the 2018/2019 school year. The success of this study was shown by an increase in learning outcomes of 72.38 with 76.19% classical completeness and an increase in the percentage of students' mathematics learning activeness in each cycle. The results of the study concluded that the average class from cycle I to cycle II increased by 4.53 points. The average class for student learning outcomes has reached the minimum completeness criteria (KKM). Classical mastery learning students increased by 14.29%. In the learning activeness of students, there is a percentage increase of 13%. It was concluded that learning with the Realistic Mathematics Education (RME) approach can increase the activeness and learning outcomes of students.